Chagas Disease: A silent health problem in the Olmedo Cantón, Manabí province, Ecuador. - Alejandro Polanco, Carlos Regino (2024)
Chagas Disease (CD) is endemic in Ecuador, with a notable prevalence in the province of Manabí. Specifically, the Olmedo canton stands out as one of the most affected by this disease. The objective of the present study is to clinically and epidemiologically characterize the cases of CD, diagnosed from January 2019 to December 2022 in the Olmedo Canton, Manabí, Ecuador. An observational, descriptive study was carried out, registering 14 confirmed cases of Trypanosoma cruzi infection. The variables studied were the number of cases presented per year, sex, age groups, laboratory diagnosis, type of surveillance. A total of 14 reactive cases were identified; mostly represented by the male sex; with a predominance of people over 65 years of age. Active surveillance contributed to the highest number of notifications. The total number of cases corresponded to chronic Chagas disease. The communities of San Roque and the Divino Niño neighborhood presented the highest number of notifications of confirmed cases. In conclusion, it is proposed that Chagas Disease represents a silent health problem in the Olmedo Canton. Active surveillance through case search, as well as antibody tests, are key in diagnosis.